A Randomized Clinical Trial of Alcohol Care Management Delivered in Department of Veterans Affairs Primary Care Clinics Versus Specialty Addiction Treatment - Oslin, David W. (Springer US, 2013)
BACKGROUND: Alcohol use disorder is one of the leading causes of disability worldwide. Despite the availability of efficacious treatments, few individuals with an alcohol use disorder are actively engaged in treatment. Available evidence suggests that primary care may play a crucial role in the identification of patients with an alcohol use disorder, delivery of interventions, and the success of treatment. OBJECTIVE: The principal aims of this study were to test the effectiveness of a primary care-based Alcohol Care Management (ACM) program for alcohol use disorder and treatment engagement in veterans. DESIGN: The design of the study was a 26-week single-blind randomized clinical trial. The study was conducted in the primary care practices at three VA medical centers. Participants were randomly assigned to treatment in ACM or standard treatment in a specialty outpatient addiction treatment program. PARTICIPANTS: One hundred and sixty-three alcohol-dependent veterans were randomized. INTERVENTION: ACM focused on the use of pharmacotherapy and psychosocial support. ACM was delivered in-person or by telephone within the primary care clinic. MAIN MEASUREMENTS: Engagement in treatment and heavy alcohol consumption. KEY RESULTS: The ACM condition had a significantly higher proportion of participants engaged in treatment over the 26 weeks [OR = 5.36, 95 % CI = (2.99, 9.59)]. The percentage of heavy drinking days were significantly lower in the ACM condition [OR = 2.16, 95 % CI = (1.27, 3.66)], while overall abstinence did not differ between groups. CONCLUSIONS: Results demonstrate that treatment for an alcohol use disorder can be delivered effectively within primary care, leading to greater rates of engagement in treatment and greater reductions in heavy drinking.